2001
DOI: 10.1007/s003350010240
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression, genomic localization, and enzymatic activities of the mouse homolog of prostate-specific membrane antigen/NAALADase/folate hydrolase

Abstract: Human Prostate Specific Membrane Antigen (PSMA), also known as folate hydrolase I (FOLH1), is a 750-amino acid type II membrane glycoprotein, which is primarily expressed in normal human prostate epithelium and is upregulated in prostate cancer, including metastatic disease. We have cloned and sequenced the mouse homolog of PSMA, which we have termed Folh1, and have found that it is not expressed in the mouse prostate, but primarily in the brain and kidney. We have demonstrated that Folh1, like its human count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
114
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(124 citation statements)
references
References 1 publication
7
114
0
1
Order By: Relevance
“…32 Using this paradigm, we have immunized mice with xenogeneic human PSMA (hPSMA), which shares 85% identity with mouse PSMA (mPSMA) at the amino acid level and has a similar tissue distribution. 33,34 This pattern of expression supports the clinical relevance of a murine model that targets mPSMA.…”
supporting
confidence: 57%
“…32 Using this paradigm, we have immunized mice with xenogeneic human PSMA (hPSMA), which shares 85% identity with mouse PSMA (mPSMA) at the amino acid level and has a similar tissue distribution. 33,34 This pattern of expression supports the clinical relevance of a murine model that targets mPSMA.…”
supporting
confidence: 57%
“…Human GCP II appears identical to hPSMA and FOLH1 based on cDNA sequence, enzymatic activity and immunoreactivity (Pinto et al, 1996;Luthi-Carter et al, 1998;Halsted et al, 1998;Bacich et al, 2001;Watt et al, 2001). Previous studies reported that 2 Kb and 1.2 Kb of the 5′ promoter of the PSMA gene were effective in driving reporter gene expression in prostate-derived cell lines and non-prostate cell lines but not in CNS-derived cell lines (O'Keefe et al, 1998;Good et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, GCP II is primarily, if not exclusively, expressed in astrocytes (Slusher et al, 1992;Berger et al, 1999;Ghose et al, 2004;Sacha et al, 2007). Enzymatic and molecular cloning studies further suggest that GCP II expressed in the human cerebellum, prostate specific membrane antigen (PSMA) expressed on hormone refractory metastatic prostate cancer cells (Israeli et al, 1993), and folate hydrolase I (FOLH1) in the small intestine are identical proteins (Pinto et al, 1996;Luthi-Carter et al, 1998;Halsted, et al,1998;Bacich et al, 2001;Watt et al, 2001). However, their biological functions may significantly differ.…”
Section: Introductionmentioning
confidence: 99%
“…All the antibodies also reacted with prostate epithelial cells in formalin-fixed prostate tissue (Figure 1). Since mouse and rat kidneys express glutamate carboxypeptidase, 17,18 this tissue was used to test the specificity of 24.4E6 and 14.3C8. Mouse and rat renal cortical tubule cells were stained with 14.3C8, but not with 24.4E6 (photos not shown).…”
Section: Characterization Of Mabmentioning
confidence: 99%